Sistem Pendukung Keputusan Pengangkatan Karyawan Tetap PT. Triagung Abadi Menggunakan Metode Analytical Hierarchy Procces (Ahp) - Putri Permata Sari (Cattleya Darmaya Fortuna, 2021)
The development of information technology today requires fast and accurate information in its implementation. The appointment of employees who perform well with the support of a decision support system is one of the implementations of the development of information technology. Research that uses the AHP method in this decision support system produces an application for an appointment decision support system that can be used in companies. The criteria used in the decision support system for the appointment of employees are: Quality of work of employees. The results of this study are to produce a ranking order of prospective employees who have good performance who have been selected, and the output of the application can assist decision makers in choosing alternative employee appointments. The application in this research is implemented using the VB programming language. NET 2008 and databases using Mysql. The Analytical Hierarchy Process (AHP) method is a method used in the design of a decision support system. The concept used by the AHP method is to change the value of a qualitative Decision Support System into a quantitative value. So that the decisions taken can be more objective. By using this Analytical Hierarchy Process, it is hoped that the employee appointment process will be more effective and efficient so that the company's leaders quickly get the value of employees who will be appointed as permanent employees to get the expected results.